2022
DOI: 10.48550/arxiv.2201.07811
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cool circumgalactic gas in galaxy clusters: connecting the DESI legacy imaging survey and SDSS DR16 MgII absorbers

Abhijeet Anand,
Guinevere Kauffmann,
Dylan Nelson

Abstract: We investigate the cool gas absorption in galaxy clusters by cross-correlating Mg absorbers detected in quasar spectra from Data Release 16 of the Sloan Digital Sky Survey (SDSS) with galaxy clusters identified in the Dark Energy Spectroscopic Instrument (DESI) survey. We find significant covering fractions (3 − 5 % within 𝑟 500 ), ∼ 4 − 5 times higher than around random sightlines. While the covering fraction of cool gas in clusters decreases with increasing mass of the central galaxy, the total Mg mass with… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 100 publications
(186 reference statements)
0
3
0
Order By: Relevance
“…Recently, Artale et al (2022) found that Mg II, C II, and Si IV are efficient tracers of the halo gas in dense environment, whereas Ne VIII, N V, O VI, and C IV are better tracers of warm hot and low-density gas (WHIM) inside filamentary structure at large scales (and z=0). In particular, the small fraction of halo gas phase inside clusters (with T < 10 5 K and n H > 10 −4 cm −3 ) is supposed to be condensed gas inside halos in high-density and low-temperature star-forming regions, as recently observed via Mg II absorption lines by Lee et al (2021), Anand et al (2022), andMishra &Muzahid (2022). For example, Lee et al (2021) showed that Mg II absorbers are more abundant inside clusters than outside them (> 2R 200 ).…”
Section: The Gas Phasesmentioning
confidence: 82%
“…Recently, Artale et al (2022) found that Mg II, C II, and Si IV are efficient tracers of the halo gas in dense environment, whereas Ne VIII, N V, O VI, and C IV are better tracers of warm hot and low-density gas (WHIM) inside filamentary structure at large scales (and z=0). In particular, the small fraction of halo gas phase inside clusters (with T < 10 5 K and n H > 10 −4 cm −3 ) is supposed to be condensed gas inside halos in high-density and low-temperature star-forming regions, as recently observed via Mg II absorption lines by Lee et al (2021), Anand et al (2022), andMishra &Muzahid (2022). For example, Lee et al (2021) showed that Mg II absorbers are more abundant inside clusters than outside them (> 2R 200 ).…”
Section: The Gas Phasesmentioning
confidence: 82%
“…The gas at these temperatures is traced by ions such as MgII at ∼ 10 4 K (Anand et al 2021(Anand et al , 2022, SiIV at∼ 10 5 K (Zheng et al 2017) and OVI at ∼ 10 5.5 K (Tumlinson et al 2011). We refer the reader to fig.…”
Section: Cgm Casementioning
confidence: 99%
“…The trends are similar but weaker for C IV. Anand et al (2022) associated Mg II absorbers at 0.4 < 𝑧 < 1 with galaxies in cluster environments, looking for correlations between their strength and the traits of the brightest cluster galaxy (BCG) as well as with the nearest satellite galaxies. The Mg II systems are closer on average to satellite galaxies than a random distribution of Mg II, suggesting a physical association.…”
Section: Comparison To Observational Studiesmentioning
confidence: 99%